Alternatif Penghasil Energi Listrik Menggunakan Aplikasi Mobile Berbasis Microcontroller - Afira, Riandana (Riset Sinergi Indonesia (RISINDO), 2023)
The development of science and technology (IPTEK) in the world of electronics and telecommunications is currently experiencing very significant progress, this is evidenced by the existence of a variety of new and sophisticated inventions that can minimize time and energy not only used for computers, era globalization requires humans to create a control system that makes it easier for humans to use it. The damage produced by livestock waste to communities around rivers is livestock waste that is disposed of into rivers will damage river water because the waste will dissolve in river water and can destroying communities that use rivers as a resource for them. Therefore this system is made by designing, manufacturing and implementing system components which include a microcontroller as a controller, a thermocouple sensor is used to measure the temperature resulting from burning livestock waste. Peltier modules and solar cells are the main energy producers in thermoelectric generators. The voltage sensor is used to measure how much voltage is generated which will be displayed in the application menu. HC-05 Bluetooth module as a liaison between the microcontroller and the mobile application via a smartphone. Buzzer and Led as indicators on the battery when the battery is only 20% left. Batteries as a storage medium for power generated from the burning of livestock waste. The results showed that the tools that were made could function properly and could be developed for a larger scale.